المسيح بن يوسف في التراث اليهودي الديني - Badran, Muhammad (Fatih Sultan Mehmet Vakıf Üniversitesi, 2023)
شغلت نهاية الزمان الإنسان منذ فجر التاريخ، وقد مان له في ذلك إجابات منها المنزلة ومنها الوضعية، وشغله فيما شغله كل ما ارتبات بها من أحداثو شخصيات، بين المروي المنصوص، وبين المقدس والمجتهد، و قد حاولت التفسيرات الدينية تقديم تصور عما سيحصل مبنياعلى النصوص الدينية، كانت منزلة أو متخيلة.

Zamanın sonu, tarihin başlangıcından beri insanı meşgul etmiştir. Statü ve pozitivizm dahil olmak üzere buna pek çok cevap verilmeye çalışılmıştır. Gerek olaylar ve şahıslar, gerek rivayetler ve Metinler ve gerekse kutsi inanç ve pozitif çabalar açısından çokları bu konuyla meşgul olmuştur.

Man has been preoccupied with the end of time since the dawn of history. Many various heavenly and earthly answers have been proposed. Many people have been deeply absorbed in thought with the apocalypse, in terms of events, figures, narrations, and both sacred and diligent texts.
Yahudi Dini Mirasında Mesih B. Yusuf
The Messiah Son of Joseph in The Jewish Religious Heritage
Keywords: المسيح بن يوسف; المسيح بن داود; الزوهار; هار مجدون; أرميليوس; Messiah; Ben Yusuf; Ben Dawoud; Zohar; Har Mecdun; Aremilos; Messiah Ben Youssef; Messiah Ben Dawoud; Zohar; Har Majdun; Armelios